Polymerase chain reaction targeting 16S ribosomal RNA for the diagnosis of bacterial meningitis after neurosurgery (Clinics, 2021)
OBJECTIVES: Bacterial and aseptic meningitis after neurosurgery can present similar clinical signs and symptoms. The aims of this study were to develop and test a molecular method to diagnose bacterial meningitis (BM) after neurosurgery.METHODS: A 16S ribosomal RNA gene PCR-based strategy was developed using artificially inoculated cerebrospinal fluid (CSF) followed by sequencing. The method was tested using CSF samples from 43 patients who had undergone neurosurgery and were suspected to suffer from meningitis, and from 8 patients without neurosurgery or meningitis. Patients were classified into five groups, confirmed BM, probable BM, possible BM, unlikely BM, and no meningitis.RESULTS: Among the samples from the 51 patients, 21 samples (41%) were culture-negative and PCR-positive. Of these, 3 (14%) were probable BM, 4 (19%) were possible BM, 13 (62%) were unlikely BM, and 1 (5%) was meningitis negative. Enterobacterales, non-fermenters (Pseudomonas aeruginosa and Acinetobacter baumannii), Staphylococcus haemolyticus, Granulicatella, Variovorax, and Enterococcus cecorum could be identified. In the group of patients with meningitis, a good agreement (3 of 4) was observed with the results of cultures, including the identification of species.CONCLUSION: Molecular methods may complement the diagnosis, guide treatment, and identify non-cultivable microorganisms. We suggest the association of methods for suspected cases of BM after neurosurgery, especially for instances in which the culture is negative.